Concept, development and implementation of islamic management standards in malaysian education institutions - Mohd Ali, Hairuddin (The School of Postgraduate, State Islamic University, Mulana Malik Ibrahim (UIN) Malang, Indonesia, 2012)
The purpose of this paper is to present the concept, development and the implementation of Islamic Management Standards in Malaysia Education Institutions particularly by the universities and community colleges. The experience from their implementations of the standards is described. This paper tried t highlight the implementation of the Islamic Management System Standards (MS 1900:2005) among three institutions of higher learning using a simple and brief case studies. Every institutions involved in this case study (the name of the institutions are not revealed due to confidentiality) were contacted and interviewed verbally using the phone. In getting more exact and rich data, a data collection protocol, open ended questions were sent to the quality managers using their official emails. However, instead of all three Islamic management system standards certified educational institutions, only two agreed to participate (Educational Institutions A and C). The case study revealed that the Islamic Management Standards scope of implementation for both case educational institutions were differ whereby A only focused on physical part while its counterpart focused on the overall management of the case educational institutions. There were also other findings which involve the future sustainability of the case educational institutions. The finding from the case study at least provide some information about how this Islamic management system standards are employed and implemented to this far and this will questionably implicate the future employment of such management standards by other educational institutions locally and globally.